The role of environmental governance in enhancing the disclosure of financial information related to climate change: A proposed framework under of international standards (Entrepreneurship Journal for Finance and Business, 2025)
The aim of the research is to study and analyze the role of environmental governance in enhancing and activating accounting disclosure of financial information related to climate change, in light of international standards issued by professional organizations such as the SASB standards, GRI standards, and others.On the practical side, the researcher tested the impact of environmental governance on the disclosure of financial information related to climate change through an electronic questionnaire, where 82 forms were distributed to a number of academics in Iraqi universities, as well as professionals (accountants and auditors) working in both the public and private sectors. The results were analyzed using the SPSS program.The research reached several conclusions, the most important of which is that improving the level of environmental governance contributes to enhancing corporate transparency and increasing investor and stakeholder confidence in financial information related to climate change.The research also presented a number of recommendations, the most notable of which is the need to benefit from international experiences in adopting governance principles in general, and environmental governance in particular, in order to activate disclosure and increase transparency regarding environmental issues, sustainable development, and climate change.